Identificação e caracterização de SNPs no genoma de Eugenia dysenterica DC. (Myrtaceae) - Nunes, Rhewter (2015)
The cagaiteira (Eugenia dysenterica DC), belonging to the Myrtaceae family, is a neotropical fruit tree species and native Brazilian Cerrado. As for the vast majority of neotropical species, very little is known about the genome of cagaiteira and genetic studies conducted so far are based on the use of a small number of molecular markers. In order to facilitate the development of genetic analysis studies in genomic scale for the species, this study aimed to identify and characterize variants of a single nucleotide (SNPs) in the genome of E. dysenterica using next-generation sequencing data. Genomic DNA libraries extracted from leaf tissue of five individuals of E. dysenterica, descendants of five distinct natural populations were subjected to sequencing on Illumina MiSeq platform, using the paired-end strategy (2x300). The sequences obtained were submitted to quality control examination to remove adapters and low quality regions. An assembly for the draft genome of E. dysenterica was produced by use of dipSPAdes program. To identify SNPs, after controlling for data quality, we performed the alignment of the assembly reads the draft with the BWA program and variants were identified using the platform of GATK tools. After three stages of filtration were identified 999,016 SNPs, with a Ts / Tv ratio equal to 1.86. We observed a density of one SNP every ~ 251 bases and most SNPs occurs in the context gene (59.79%). Most effects of putative SNPs identified are missense mutations (57.70%), but which have a low impact (0.74%). This work provides subsidies for the development of molecular markers for application in genomic studies of populations of E. dysenterica.